Family Support on Exclusive Breastfeeding in Babies Aged 0-6 Months in Indonesia: Literature Review - Hanny Rasni; Kholid Rosyidi Muhammad Nur; Dodi Wijaya; Grace Pakilaran (KHD-Production, 2022)
The beneficial of breastfeeding can be felt by baby and its mother. The national scope of giving breastmilk in 2018 is 32,3%. However, the national scope target for breastmilk set by the Ministry of Health, is 80%. In exclusive breastfeeding, mother needs support from the family as closest neighborhood. This study aim to identify publications that provide information on concepts and data relevant to the topic of family support for exclusive breastfeeding in Indonesia. This study uses a literature review design with 3 search enginees: Science Direct, Google Scholar, and PubMed. The total of 12 selected articles with a cross-sectional approach has population of mother and baby aged 0-24 months. The results of the article analysis shows that 9 articles stated that there were relationship between family support and exclusive breastfeeding. Then, 3 articles stated that there were no relationship between family support and exclusive breastfeeding. Support that comes from husband and other family members can increase mother's ability to give exclusive breastfeeding, a sense of calm and comfortable. Thereby, it also can increase production of the hormone oxytocin and affect breastmilk production. In addition, family support can increase confidence in exclusive breastfeeding. By continously giving an exclusive breastfeeding for 6 months, can provide benefits for both mother and baby. The nursing implication that can be done is to provide health education to mother regarding exclusive breastfeeding as the main source of food and the best nutrition for babies in a first 6 months.